Encoding medieval abbreviations for computer analysis (from Latin-Portuguese and Portuguese non-literary sources) - Parkinson, S; Emiliano, A (Oxford University Press, 2002)
This paper proposes a solution to the problem of handling scribal abbreviations in TEI-conformant transcriptions of medieval texts, following a conservative editorial strategy. A key distinction is drawn between alphabetic abbreviations, which represent sequences of letters, and logographic abbreviations which represent whole words. The TEI elements <expan> and <abbrev> can be used systematically to separate these two types: alphabetic abbreviations will be expanded in the main text, recording the abbreviated form (including TEI entities representing the main abbreviation marks) as an attribute of <expan>, while logographic abbreviations will be represented in their abbreviated form, with the expanded form recorded as an attribute of <abbrev>. The proposals are illustrated from common abbreviations and short text samples from tenth-century Latin-Portuguese and thirteenth-century Old Portuguese.</abbrev></expan></abbrev></expan>